Real-time power dispatch in a standalone hybrid multisource distributed energy system using an Arduino board - Kelebogile Confidence Meje; Lindiwe Bokopane; Kanzumba Kusakana; Mukwanga Siti (Energy Reports, 2021)
This paper presents the implementation of a real-time automated energy management control in a RE hybrid system, integrated with backup and validated in a laboratory setup. The experimental setup used a fuzzy intelligent controller for energy management on the software tool platform, the control board layout designed with aid of the Proteus Design Suite 8.1 software and the Arduino MEGA2560 hardware platform board, uploaded from Arduino integrated development Environment (IDE). The utilized hardware platform has the ability to monitor the real-time voltage dissipated by each component and is balanced by the controller via the voltage regulator, by adjusting it to an acceptable and readable voltage of 5 V by Arduino to the load. Arduino IDE has been programmed and uploaded to the hardware platform using C++ language. Furthermore, there are two different Arduino types, Arduino MEGA and Arduino UNO. Arduino MEGA2650 was selected in this study, as it has a more pin size compared to UNO and it may further accommodate a hybridized system with more components. The experimental results, therefore, was observed through experimental work that was based on the Arduino control preferences; the model capable of providing automatic supply of power to the load without human interferences, visualized in MATLAB plotting.